Evaluation of compliance of CONSORT-CHM formula 2017 in randomized controlled trials of Chinese herbal medicine formulas: protocol of a five-year review - Wang, Juan; Cheng, Chung Wah; Jiao, Yalin; Shi, Dongni; Wang, Yaochen; Li, Han; Wang, Nana; Wang, Xihong; Li, Yuqin; Liang, Feng; Luo, Shufeng; Han, Fei; et al. (Frontiers in Pharmacology, 2024)
Background: The CONSORT Extension for Chinese Herbal Medicine Formula 2017 (CONSORT-CHM Formula 2017) has established a reporting standard for randomized controlled trials (RCTs) of Chinese Herbal Medicine Formula (CHMF) interventions; however, its adherence and implications for the design and execution of study design remain ambiguous. It is necessary to evaluate the level of compliance with the CONSORT-CHM Formula 2017 in RCTs conducted over the past 5 years, and to determine the reporting quality of clinical trials in this field. Methods: First, a systematic search is conducted for RCTs on CHMF in EBM Reviews, Allied and Complementary Medicine (AMED), Embase, Ovid-MEDLINE(R), Wanfang data, China National Knowledge Infrastructure (CNKI), VIP Chinese Medical Journal Database (VIP) and Chinese Biomedical Literature (CBM) database, that encompassed CHMF interventional RCTs published from 1 January 2018 to 8 June 2022, with language restriction to English or Chinese. Second, a descriptive analysis will be performed regarding the study design and general characteristics of the included trials. Third, for the quality assessment, we have subdivided the CONSORT-CHM Formula 2017 checklist (consisting of 22 extended items) into a total of 42 sub-questions to facilitate scoring, with a specific focus on the description, quality control, and safety assessment of CHMF interventions. Professional training and a pilot test on 100 randomly selected articles will be provided for all reviewers. Throughout this process, a standard operating procedure (SOP) for quality assessment will be developed to ensure consistency. Each item will be assessed by two reviewers in a paired back-to-back manner, and the compliance rate will be calculated to assess inter-rater agreement. Discussion: This review will identify the current reporting characteristics and quality of CHMF interventional studies and further evaluate the impact of CONSORT-CHM Formula 2017. The results may provide suggestions for future application or promotion of the guideline. Registration: The study has been registered on Open Science Framework (https://osf.io/xpn7f).